Hubungan antara Kebiasaan sarapan dengan Status Gizi pada siswa SMP Negeri 5 Banyuwangi - Sheila Monica Kelly Amalia; Merryana Adriani (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: The increase prevalence in obesity by 14.8 percent according to Riskesdas 2018 needs to be a public concern. Obesity in adolescents can result in a high risk of degenerative diseases in later life. One cause of obesity is breakfast habits that are often left abandoned.Objective: This study was aimed to analyze the relationship between habits of breakfast and nutritional status of students in SMP Negeri 5 Banyuwangi.Method: This study was an observational study using design of cross sectional. The sample size of this study was 37 seventh grade students of SMP Negeri 5 Banyuwangi. The method of sampling was Proportionate Stratified Random Sampling. The data were collected by interviewing using food recall 3x24 hours, habits of breakfast questionnaire, and nutritional status was determined based on BMI for age measurements. Data analysis was performed to determine the frequency distribution and the percentage of each variable studied. The statistical analysis used is a regression test.Results: The results showed that most students had good habits of breakfast (91.9%), normal nutritional status (72.9%). The regression test results show that there was a correlation between habits of eating breakfast and nutritional status (p=0.049). Conclusion: Breakfast habits related to nutritional status of students of SMP Negeri 5 Banyuwangi.Keywords: breakfast habits, nutritional status, adolescentsABSTRAKLatar Belakang: Salah satu masalah yang dapat mengancam masa depan remaja di Indonesia yaitu masalah yang terkait dengan status gizi yakni kurus atau kurang energi kronis (KEK) dan kegemukan atau obesitas.Tujuan: Penelitian ini bertujuan menganalisis hubungan antara kebiasaan sarapan dengan status gizi pada siswa SMP Negeri 5 Banyuwangi.Metode: Jenis penelitian ini merupakan penelitian observasional dengan metode pendekatan cross sectional. Besar sampel penelitian ini adalah 37 siswa kelas VII SMP Negeri 5 Banyuwangi. Cara pengambilan sampel dengan Proportionate Stratified Random Sampling. Pengambilan data dilakukan dengan wawancara menggunakan kuesioner kebiasaan sarapan, dan status gizi ditentukan berdasarkan pengukuran IMT/U.Hasil: Hasil penelitian menunjukkan sebagian besar siswa memiliki kebiasaan sarapan baik (91,9%), status gizi normal (72,9%). Hasil uji regresi menunjukkan bahwa adanya hubungan pengetahuan gizi dengan kebiasaan sarapan (p=0,049).Kesimpulan: Kebiasaan sarapan berhubungan dengan status gizi siswa SMP Negeri 5 Banyuwangi.